The effects of the upright body type exercise program on foot plantar pressure of archers - Kim, D.-K.; Lee, J.-S. (Korean Journal of Sport Biomechanics, 2016)
Objective: This study collected data on muscle fatigue and ground reaction force during walking to provide a basis for development of custom-fitted outdoor walking shoes. The study analyzed an upright body exercise program using spine stabilization technique to determine the effect on foot plantar pressure in archers, demonstrate the effectiveness of upright body exercise, and develop a new, effective, and efficient training program. Method: A 12-week upright body exercise program was evaluated for the effect on plantar pressure in archers. Ten prize-winning archers (3 men, 7 women) in B metropolitan city, each with =10 years of experience, were given an explanation of the content and purpose of the program, and provided informed consent. Upright body exercise was performed 3 times a week for 12 weeks. A resistive pressure sensor was used to measure foot plantar pressure distribution and analyze quantitative information on variation in postural stability and weight shifting in dynamic balance during shooting, as well as plantar pressure in static balance with the eyes open and closed. Results: There were no significant differences in foot plantar pressure before and after participation in the exercise program. There was no statistically significant difference in foot plantar pressure in static balance with the eyes open or closed, or in foot plantar pressure in dynamic balance during shooting. Conclusion: An upright body exercise program had positive effects on foot plantar pressure in static and dynamic balance in archers by reducing body sway and physical imbalance during shooting and with eyes closed. This program is expected to help archers improve their posture and psychological state, and thereby improve performance.